Los componentes material y finalista de la fiscalización administrativa: aproximaciones desde la doctrina, la normatividad y el control jurisdiccional efectuado en sede suprema - Cuba, Erick; Arévalo, Carlos (Pontificia Universidad Católica del Perú, 2025)
Based on the doctrinal constructions and legal provisions related to administrative oversight, this paper analyzes the foundations of this activity, its current regulation, as well as its two defining components: the material execution and its purpose. Both components, material and final have been the subject of evaluation in the Supreme Court's cassations that have dealt with administrative oversight. Thus, this paper presents how these components have been safeguarded through jurisdictional control,having analyzed in the cases subject to litigation the rules that ensure its elements, taking as a reference the legal parameter of duties and obligations established in the current regulation contained in the Single Ordered Text of the Law of Sanctioning Administrative Procedure.

A partir de las construcciones doctrinarias y las disposiciones legales referidas a la fiscalización administrativa, el presente trabajo analiza los fundamentos de dicha actividad, su actual regulación, así como sus dos componentes definitorios: la ejecución material y su finalidad. Ambos componentes, material y finalista, a su vez, han sido el tema de evaluación en las casaciones de la Corte Suprema que han tratado la fiscalización administrativa. De esta manera, en este trabajo se presenta cómo es que estos componentes han sido cautelados mediante el control jurisdiccional, al haber analizado en los casos materia de litis las reglas que aseguran sus elementos tomando como referencia el parámetro legal de deberes y obligaciones establecidos en la regulación actual contenida en el Texto Único Ordenado de la Ley de Procedimiento Administrativo Sancionador.
The material and final components of administrative oversight: approaches from doctrine, regulations and jurisdictional control carried out in the supreme court
Keywords: Oversight; Material execution; Purpose; Control; Legal parameter; Duties; Powers; Obligations; Fiscalización; Ejecución material; Finalidad; Control; Parámetro legal; Deberes; Facultades; Obligaciones; https://purl.org/pe-repo/ocde/ford#5.05.00